The Development of a Canva-Based E-Module for Indonesian Language Learning on Inspirational Story Texts at SMP Negeri 2 Koto Baru: A Literature Review - Aprimadedi, Aprimadedi; Marlianda, Rendi; Sari, Yustri Arsita (The Future of Education Journal, 2026)
This research will analyze the need for developing an e-module design for inspirational story texts in Indonesian language learning. This needs analysis is part of research and development (R&D). The research method used is descriptive qualitative. The subjects of this research were class IX students. Data collection was carried out by observation, interviews, questionnaires and document analysis. Data analysis was carried out using descriptive analysis, namely the feasibility of teaching e-modules by experts, the feasibility of the material by material experts accompanied by responses from teachers. The research results show that the required learning resources are easy to learn in digital form. The development of an e-module based on the Canva application on inspirational story text material aims to attract students' interest and make learning fun by using technology.